Complete genome sequence of Pasteurella multocida serotype s strain PMTB2.1 isolated from buffaloes that died of septicemia in Malaysia - Jabeen, Shagufta; Yap, Huan Yong; Abdullah, Faez Jesse Firdaus; Zakaria, Zunita; Mat Isa, Nurulfiza; Tan, Yung-Chie; Yee, Wai-Yan; Omar, Abdul Rahman (American Society for Microbiology, 2017)
Pasteurella multocida causes pneumonic pasteurellosis and hemorrhagic septicemia (HS) in large ruminants. In this study, we determined the complete genome sequence of P. multocida strain PMTB2.1 capsular serotype A isolated from buffaloes that died of septicemia.